Stanford health briefings the optimal diet for overall health - Guillo, Robert; Guillo, Robert (California : Kantola Productions, 2002)
This video present about acknowledging that nutrition studies by Dr. Gardner's. Focuses on overall dietary pattern that concentrate on the goog things you should include.
Copy available in DVD format
Executive producers, Wesly F. Alles, Catherine O' brien and Steve Kantola; editor, Robert Guillo and Melissa Peabody
Keywords: Diet; Communication in diet therapy